Assessing the Influence of Digital Marketing Communications on Customer Loyalty: The Moderating Role of Service Quality: Evidence from Sudanese Companies - Helal, Tarig Osman Abdallah; Alnor, Nasareldeen Hamed Ahmed; Benlaria, Houcine; Hamad, Abualhassan Jumaa Hamid; Abdelfadel, Tagreed Awad Abdelhalim; Youseif, Nuseiba Azzam Ibrahim (Journal of Cultural Analysis and Social Change, 2025)
The factor of this observe is to inspect how virtual marketing messages have an effect on patron loyalty and the way provider satisfactory influences that courting within the Sudan Telecom Company. Using a quantitative studies method, facts become accumulated from a large institution of clients to investigate how the have a look at's essential variables were related to each other. According to the study, virtual advertising communications play a huge part in making clients extra loyal. This means that good on-line exchanges, promotional messages, and engagement all play a massive component in clients' lengthy-time period dedication to the organization. Additionally, the consequences show that provider quality is a key part of constructing loyalty, each at once and with the aid of making the high-quality consequences of virtual advertising messages even more potent. These phrases imply that digital marketing works even higher at preserving human beings unswerving once they assume the provider is good. Overall, the observe suggests how critical it is for telecom carrier companies to have each nicely-idea-out digital advertising plans and regularly high service requirements. In a completely aggressive market, this may make the consumer revel in better, construct agree with, and cause stronger, longer-lasting client relationships.